2022
DOI: 10.1088/1361-665x/ac736d
|View full text |Cite
|
Sign up to set email alerts
|

Fibre-optic measurement of strain and shape on a helicopter rotor blade during a ground run: 1. Measurement of strain

Abstract: Optical fibre strain and shape measurement sensors were deployed on a 5-m long rotor blade during a full-speed (rotation rate 6.6 Hz) helicopter ground run, with real-time data wirelessly streamed from rotor hub-mounted sensor interrogators. In part 1 of a 2-part paper series, the strain sensing capabilities of the two optical fibre-based sensing techniques, optical fibre Bragg grating (FBG) and fibre segment interferometry (FSI), are compared, while Part 2 [1] specifically investigates the blade shape measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…As shown in Part 1 [27], long-gauge length strain sensors interrogated using our range-resolved interferometry (RRI) signal processing technique [28] offer spatially resolved, fast (≫kHz) and highly sensitive (≪nanostrain • Hz −0.5 ) strain measurements using weakly reflecting in-fibre reflectors in an approach termed fibre segment interferometry (FSI) [29], where sensor gauge lengths can range from centimeters [30] to metres [31]. RRI employs an optically simple setup without moving parts, exploiting sinusoidal wavelength modulation through injection-current modulation of robust telecoms distributed feedback laser diodes.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…As shown in Part 1 [27], long-gauge length strain sensors interrogated using our range-resolved interferometry (RRI) signal processing technique [28] offer spatially resolved, fast (≫kHz) and highly sensitive (≪nanostrain • Hz −0.5 ) strain measurements using weakly reflecting in-fibre reflectors in an approach termed fibre segment interferometry (FSI) [29], where sensor gauge lengths can range from centimeters [30] to metres [31]. RRI employs an optically simple setup without moving parts, exploiting sinusoidal wavelength modulation through injection-current modulation of robust telecoms distributed feedback laser diodes.…”
Section: Introductionmentioning
confidence: 94%
“…In this paper, interferometric DFOSS [23] in the rotating frame is demonstrated using a custom-designed interrogation unit. The general setup of the rotor-mounted instrumentation, the wireless data transfer, the technical parameters of the interferometric interrogation unit and FBG-based reflector inscription are detailed in Part 1 [27], while specific aspects relevant to DFOSS are discussed in the following. Figure 1(a) shows the bottom side of the blade with the DFOSS sensing rod attached.…”
Section: Dfoss Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical sensors, which can include optical fiber-based sensors, have also found applications in feeding back real-time measurements of weight distribution, reliable aviation fuel gauging sensors, or even water content detection and online monitoring in aviation fuel. Further, the distributed optical sensors are able to test the structural integrity of the wings and fuselage (following the four SHM levels mentioned), as well as judge the performance of the engines, icing on the wings, loading on the landing gear, and very importantly, the cockpits environment (not only in commercial aircrafts, but also military ones) [ 191 , 192 , 193 ]. In this way, with the continuous development of autopilot systems and flight assistance systems, pilot performance and air safety from the cockpits (temperature, humidity, pressure, and also detecting biological contaminants aboard aircrafts, for example) need to be improved significantly.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…3,4 Since this signal processing technique can identify individual interferometers from an interferogram of multiple optical cavities, it can therefore be used for interrogating different interferometer designs that are adapted for measuring specific physical parameters. 4,5 Recent work 6 has shown that this processing technique is a reliable, robust approach and would be suited for use in a wind tunnel environment. In this paper, we show that the key parameters of pressure, strain, and vibrational frequency can all be measured on a high-lift wing during a wind tunnel trial, via optical fibre-based sensors, using only the signal processing technique of RRI.…”
Section: Introductionmentioning
confidence: 99%